King David : a biography - McKenzie, Steven L., 1953- (Gale virtual reference library., 2000)
This is a critical biography of the biblical figure of David, concluding that he was a real person and an important historical figure. However, this reading of the biblical text also concludes that he was a very different figure to that popularly supposed.